How to Apply Statistical Software in Doing Multilevel Modeling: A Comparative Study Perspective. (September 2020) - Lin, Liming; Zhang, Xiaosan
Abstract: Multilevel model methodology is widely used in social science. There are many textbooks and h papers introducing the principles and methods of multilevel model. However, most of them are simply a brief instruction how to apply statistical software to run multilevel model, which brings some obstacles for beginners in empirical research. To address this gap, this paper aims to help beginners and common users to grasp the operation skills of multilevel model in these statistical software. Firstly, the operation procedure of multilevel model in eight statistical software are introduced. Secondly, this paper systematically compares the output results of multilevel models of these statistical software. Finally, some operational guidelines and suggestions are put forward for the empirical application of multilevel model.